Predators and the breeding bird: behavioral and reproductive flexibility under the risk of predation - Lima, Steven L. (Biological reviews of the Cambridge Philosophical Society, 2009)
ABSTRACT A growing body of work suggests that breeding birds have a significant capacity to assess and respond, over ecological time, to changes in the risk of predation to both themselves and their eggs or nestlings. This review investigates the nature of this flexibility in the face of predation from both behavioural and reproductive perspectives, and also explores several directions for future research. Most available work addresses different aspects of nest predation. A substantial change in breeding location is perhaps the best documented response to nest predation, but such changes are not always observed and not necessarily the best strategy. Changes in nesting microhabitat (to more concealed locations) following predation are known to occur. Surprisingly little work addresses the proactive avoidance of areas with many nest predators, but such avoidance is probably widespread. Individual birds could conceivably adopt anti‐predator strategies based on the nest predators actually present in an area, but such effects have yet to be demonstrated. In fact, the ways in which birds assess the risk of nest predation is unclear. Nest defence in birds has historically received much attention, but little is known about how it interacts with other aspects of decision‐making by parents. Other studies concentrate on predation risk to adults. Some findings suggest that risk to adults themselves influences territory location, especially relative to raptor nests. An almost completely unexplored area concerns the sorts of social protection from predators that might exist during the breeding season. Flocking typical of the non‐breeding season appears unusual while breeding, but a mated pair may sometimes act as a “flock of two”. Opportunistic heterospecific sociality may exist, with heterospecific protector species associations more prevalent than currently appreciated. The dynamics of singing during the breeding season may also respond to variation in predation risk, but empirical research on this subject is limited. Furthermore, a few theoretical and empirical studies suggest that changes in predation risk also influence the behaviour of lekking males. The major influence of predators on avian life histories is undoubtedly expressed at a broad phylogenetic scale, but several studies hint at much flexibility on an ecological time scale. Some species may forgo breeding completely if the risk of nest predation is too high, and a few studies document smaller clutch sizes in response to an increase in nest predation. Recent evidence suggests that a female may produce smaller eggs rather than smaller clutches following an increase in nest predation risk. Such an increase may also influence decisions about intraspecific brood parasitism. There are no clear examples of changes in clutch/egg size with changes in risk experienced by adults, but parental responses to predators have clear consequences for offspring fitness. Changes in risk to adults may also influence body mass changes across the breeding season, although research here is sparse. The topics highlighted herein are all in need more empirical attention, and more experimental field work whenever feasible.